Analisis Perilaku Konsumtif dalam Perspektif Psikologi Islam - Riskawati Saleh; Wantini Wantini; Ahmad Muhammad Diponegoro (Al-Qalb : Jurnal Psikologi Islam, 2023)
Consumption patterns at this time began to change towards consumptive behavior; this was influenced by the pace of technological development at the time, both in terms of technology and the internet, which provide various conveniences for shopping, as well as the industrial and production sectors, which offer various types of goods in shopping centers. The purpose of this research is to analyze consumptive behavior from the perspective of Islamic psychology. This research uses descriptive qualitative methods in the form of library research. Data collection was carried out by identifying key terms in a literature search, tracing and finding various sources of literature, both books and journal articles, and selecting their suitability for inclusion in the writing review. Data analysis is done by analyzing the contents of documents. The results of this study indicate that consumptive behavior in Islam is born from an instinct or urge to have something, and if this urge is not controlled, it will lead to the emergence of consumptive behavior. In the study of Islamic psychology, there are two concepts that can be instilled in individuals so they can control the emergence of consumptive behavior, namely, patience, which includes the ability to self-control, and gratitude, which evokes attitudes and behaviors of gratitude for all conditions, so that this minimizes impulsive behavior in shopping and forms individual personalities that can think long before engaging in consumption activities, namely, thinking about fulfilling needs and wants.